Training program of tools used for foresight analysis and impact assessment in the livestock sector - Enahoro, Dolapo K.; Bahta, Sirak T.; Guthiga, Paul M.; Rich, Karl M. (2021)
In many low- and middle-income countries, the livestock sector has an essential role to play in economic growth and development, livelihoods and employment creation, diets, and household nutrition, amongst others. The sector is also an important contributor to the (negative and positive) impacts of agricultural activity on natural resources such as land and water systems. ILRI scientists have been on the forefront of contributing important analyses needed to understand the multi-faceted opportunities for and impacts of the livestock sector in development, including through support to countries on their national livestock master plans. A critical part of this work is the development of readily deployable analytical tools for livestock foresight and policy. These tools are used to measure impacts of livestock investments and policies while considering biological, social, and economic dimensions, and accounting for potential changes in consumer demand. This course has been designed as a platform for delivering the analytical models developed at ILRI for livestock sector analysis and as a vehicle for enhancing partner capacities to design, conduct, and communicate policy research. It in addition aims to provide knowledge of relevant software, some of which are available open access for defined use.